A novel wide viewing endoscope for upper gastrointestinal screening: a pilot study - Naomi Kakushima; Kohei Takizawa; Masaki Tanaka; Noboru Kawata; Sayo Ito; Kenichiro Imai; Kinichi Hotta; Kimihiro Igarashi; Yoshihiro Kishida; Masao Yoshida; Hiroyuki Matsubayashi; Hiroyuki Ono (Endoscopy International Open, 2016)
The feasibility of full-spectrum endoscopy (FUSE) esophagogastroduodenoscopy (EGD), providing a 245-degree field of view with double imagers on the front and left side of the endoscope was evaluated. Twenty-one healthy individuals (15 male, median age, 35 years) underwent upper gastrointestinal screening using FUSE-EGD. The primary end point was the rate of successful visualization of Vater’s papilla. Secondary end points were visualization of the squamo-columnar junction (SCJ) and the anal side of the pyloric ring, and the endoscopists’ subjective evaluation of usability based on maneuverability and imaging of FUSE-EGD. The mean procedure time was 6.5 min, with a median of 91 images captured. The rate of successful visualization of Vater’s papilla was 90 % (19/21). The whole circumference of the SCJ was observed with two video monitors in all cases. The anterior anal side of the pyloric ring was observed in 29 % (6/21) of cases. However, the general impression of the usability of FUSE-EGD was that it was rather inferior to that of a standard front viewing endoscope. Although the usability requires further modification, FUSE-EGD provided excellent results for imaging Vater’s papilla and the SCJ.